PERAN GURU PAI DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI DI SDN 154 OGAN KOMERING ULU - Rusman Ependi,; Taqwatul Uliyah,; Riskun Iqbal, (UNISAN JURNAL, 2024)
Education is guidance or assistance given by adults to a child's development to reach maturity with the aim of making the child capable enough to carry out his life tasks on his own without the help of others. Education for mankind is an absolute need that must be fulfilled throughout life. Character education is a crucial aspect in education, especially in the school environment. Forming quality character in students is very important to produce a generation that has morality, positive values and good attitudes in their daily lives. In this research, Islamic Religious Education (PAI) teachers play a central role in shaping the character of students. Islamic religious education is a conscious and planned effort to prepare students to know, understand, appreciate and believe in the teachings of the Islamic religion, accompanied by guidance to respect adherents of other religions in relation to inter-religious harmony so that national unity and integrity can be realized. The aim of this research is to analyze the role of Islamic Religious Education (PAI) teachers in guiding the morals of students in class II of SD Negeri 154 Bindu Village, Peninjauan District, Ogan Komering Ulu Regency. This type of research is qualitative descriptive research. There are several methods for collecting data, namely, observation, interviews and documentation. The steps taken are data reduction, data display (data presentation), verification (drawing conclusions). From the data collected, the author analyzes it using inductive thinking which starts from a specific conclusion and then becomes a conclusion. The results of the research found that Islamic Religious Education (PAI) teachers have played a role in guiding students' morals, but their success has not been optimal because there are several inhibiting factors in the implementation of students' character formation which influence it. Because the success of character formation in students is not solely due to teacher factors but also influences, among other factors, the role of parents, environmental influences and most importantly, internal factors of students, namely the motivation of the students themselves.